Floristic composition and community structure of mid-montane evergreen broad-leaved forest in north slope of Baishanzu Mountain - XU Min; LUO Zheng-rong; YU Ming-jian; DING Bing-yang; WU You-gui (浙江大学学报. 农业与生命科学版)
A 5 hm2 permanent plot was established in an evergreen broad-leaved forest, which lies in the north slope of Baishanzu Mountain, Qingyuan of Zhejiang. Using contiguous grid quadrat method, extensive field data were obtained and analysis of floristic composition and community structure showed as following, (i) Two evergreen species, Lithocarpus brevicaudatus and Cyclobalanopsis multinervis are the constructive species within the species-rich community. (ii) Areal-type of species suggests that the forest is highly related to tropic components, while temperate components still occupy fairly high percentage. It indicates that the forest is a mid-montane evergreen broad-leaved forest in the northern subzone of the middle subtropic. (iii) Lots of rare-species exist in the community, and the dominance of the dominant species is high, but the distribution of abundance is uneven. (iv) Large amount of seedlings and saplings exhibit good regeneration, and as a result of the effects of intraspecific and interspecific competition, few individuals have super diameter at breast height (DBH). Distribution of the diameters frequency is detected as exponential distribution, which indicates the stems are continuous distribution on the vertical space, and the community is on the climax stage of succession process. (v) Community structure is complex, and the delamination is not obvious. The dominant species distribute in different two sub-layers of trees, and it lessens competition on a certain extent. Upper canopy is discontinuous, and it is far from the under-layer. The dense shrub-layer contains many species, and it is the seedling pool of the community. Herb-layer is sparse but with rich species, and liana is various but lack of large individuals. In conclusion, this community is a typical middle subtropical evergreen broad-leaved forest.